Behavior-Based Safety (BBS) and Accident Rates at Construction Sites of a Construction Company in Lima - Bracamonte Sunción, Gloria (2025)
The research problem centers on the urgent need to improve workplace safety conditions. The objective was to determine the relationship between behavior-based safety (BBS) and accident rates in the construction sites of a building company located in Lima. A quantitative approach with a non-experimental, correlational design was employed for this purpose. The sample consisted of five construction sites between 2021 and 2022. The main finding revealed a strong negative correlation between BBS and accident rates, evidenced by a correlation coefficient of −0.918. This suggests that greater BBS implementation is associated with a lower accident rate. A p-value of 0.028 confirmed the statistical significance of this relationship. In conclusion, the findings highlight the effectiveness of BBS programs in reducing occupational accidents in the construction sector.